Pertimbangan Lingkungan pada Pembangkit Listrik Tenaga OTEC (Ocean Thermal Energi Conversion) - Hendrawan, Andi (Prosiding University Research Colloquium, 2019)
Indonesia, which has the largest population among ASEAN countries, so it will become net oil imports at the beginning of the 21st century. The Indonesian government has developed a long-term energy plan that aims to diversify energy to reduce the country’s dependence on oil. One renewable energy source is utilizing differences in sea surface temperature, solar energy that creates this gradient and specifically Ocean Thermal Energy Conversion (OTEC) Ammonia is formed by a catalytic combination of 3 moles of hydrogen with 1 mole of nitrogen at high pressure and medium temperature with an iron oxide catalyst. the environmental impact of a closed cycle OTEC can be understood. The following have been identified as potentially significant: release of fluids or biocides that work in the atmosphere, impacts on threatened or endangered terrestrial or marine species, etc. Because of its irritation, these pollutants can stimulate the inflammatory process in the upper respiratory tract, which is the channel of exposure from the nose to the throat